Pengiriman Kargo Untuk Mendukung Transaksi Pengiriman Barang Untuk Peningkatan Transaksi Biaya Pengiriman Lebih Efisien - Sutini Paleon; Harcici Harcici; Yoga Septian (Dinamika Bahari, 2020)
In this research to support the needs of shipping transactions that have become the main components of each individual and and all individuals also want delivery of goods quickly and securely to ensure that delivery of goods to the place and the exact timeof land transportation and to the sea. Marketing activities, delivery of goods related to distribution, delivery of goods or services from the sender to the sender to increase delivery transactions. The right mode of transportation for freight through thesea. The purpose of this research is to choose the right path. Methods used in this study using quantitative methods. To do research in Tanjung Emas Harbour. Results of this research calculation of shipping cost of Container that is through the Green LineRp. 2,516,417,000. Calculation of shipping cost of container that through the red Line Rp. 4,404,077,320 There is a very significant difference in cost. The purpose of this research is to choose a more efficient path, the sedation method used and quantitative survey.